STUDENTS' MATHEMATICAL COMMUNICATION SKILLS IN SOLVING STORY PROBLEMS BASED ON MATHEMATICAL ABILITIES - Samawati, Ilmus (Sanata Dharma University Yogyakarta, 2021)
The research aims to describe the students' mathematical communication skills in solving story problems based on mathematical abilities. This research is descriptive qualitative research. Subjects in this research involved 3 students tenth-grade science in one of the senior high schools in Sidoarjo. Based on the mathematics scores in the last report card, I obtained one student with high mathematical abilities, medium mathematical abilities, and low mathematical abilities. The research data were obtained from mathematical communication skills tests and interviews based on a communication skills test. The results showed that students' mathematical communication skills are in line with their ability to solve problems on story problems because they are influenced by the level of mathematical ability of each student who is different in written and oral communication skills.